Developing HoPALM as teaching materials for secondary school students - Asih Sauramanda; Majid Wajdi; Iwan Supardi (Journal of English Language Teaching Innovations and Materials (Jeltim), 2021)
This research was aimed to develop a product named HoPALM, hot-potatoes assisted listening material for secondary high school students. This research applied development research and ADDIE procedure. In the analysis stage, the researcher found the fundamental problems and needs of the students as well as the opportunity as the background of developing HoPALM. In the designing and developing stage, the researcher collected the sources that needed and develop HoPALM by using the features available on the hot-potatoes program. After the product assessed by the material content and the multimedia experts, HoPALM considered as valid and applicable to use, the researcher implemented the product to the two school targets, SMA Negeri 1 and 2 Sungai Kakap. According to 208 students from two schools, as many as 156 students or 75% of them feel more motivated and prefer to learn English. As many as 123 students or 59.1% of them were able to overcome difficulties encountered. 120 students or 57.7% admitted that their listening ability increased. Furthermore, although not spontaneously, as many as 196 students or 95.6%, confessed being able to understand what they are listening to, especially if there are images in that section. Most importantly, as many as 120 students or 57.7% more motivated in learning English.